Nasal polyposis in a cow - Duarte, Roberta P. [UNESP]; Rocha, Paulo Ricardo D. [UNESP]; Schweigert, Augusto [UNESP]; Morelli, Fernando C. G. [UNESP]; Machado, Gisele F. [UNESP] (My University, 2015)
A case report of nasal polyps in an eight year-old Tabapuã cow is reported. The cow had a history of difficulty in breathing, was euthanatized and referred for necropsy. Twenty three pedunculated neoformations were observed in the nasal cavity. Microscopically, polypoid structures were composed by swollen myxomatous stroma lined by pseudostratified columnar epithelium. Immunohistochemistry was positive for cytokeratin in the cytoplasm of epithelial cells only covering the pseudo-stratified respiratory epithelium, whereas anti-vimentin antibody was positive in the cytoplasm of cells and areas of calcification of the tunica media of blood vessels and fibroblasts within the parenchyma of the polyps. The macroscopy, histopathological, and immunohistochemical findings were consistent with nasal polyps. This is the first report of nasal polyposis in a cow in Brazil.
Keywords: Bovine; Nasopharyngeal obstruction; Polyp; Upper respiratory tract